DIFFERENCE IMPLEMENTATION OF T1WI SE AND T1WI FSPGR BRAVO SEQUENTS IN MRI BRAIN TUMOR - Sulistyo, Eko; Mar’athus N, Ildsa Maulidya (Postgraduate Program , Poltekkes Kemenkes Semarang, 2019)
Tumor is basically an uncontrolled growth of cancerous cells in any part of the body, whereas a brain tumor is an uncontrolled growth of cancerous cells in the brain. Useing of MRI in diagnose tumors can be done with various sequences. Contrast medium is needed to evince tumor enhancement, as well as sequences that support to produce tumor in post contrast, one of which uses a conventional sequence T1WI SE. This sequences often lose information in providing images in cases of brain tumors and generally more time consuming. FSPGR BRAVO is a 3D volumetric acquisition that captures thin section images with near isotropic or isotropic spatial resolution. This sequence displays anatomy, especially brain parenchymal anatomy, in fine detail. The type of research in this mini research is a qualitative study with an observational approach which aims to find out sequences that can optimize post-MRI images in contrast to brain tumor cases with a short time and get the right diagnosis. Convensional sequence of MRI TIWI SE can’t detection of lessions in cerebral cortex. FSPGR BRAVO in producing images in 3D format in one-time retrieval of one particular piece and able to display anatomy especially the anatomy of the brain parenchyma in fine detail. FSPGR BRAVO can be used to assist cause to be uprise the diagnosis of MRI brain tumor by displaying the anatomy of the brain parenchyma in more fine detail, without the need for extended time.